Nieuwe Monumenten = New Monuments. - Désanges, Guillaume; Gielen, Pascal; Gregos, Katerina; Middelheimmuseum, Antwerpen (Antwerpen : Ludion Gent Middelheimmuseum Antwerpen, 2010)
Coolen, Caroline ; Creten, Johan ; De Cock, Jan ; Ervinck, Nick ; François, Michel ; Geers, Kendell ; Meuris, Wesley ; Mutlu, Selçuk ; Muyle, Johan ; Naveau, Nadia ; 't Jolle, Sven ; Vergara Santiago, Angel ; Verhoeven, Gert
Engels
Nederlands
Catalogus n.a.v. de tentoonstelling 'Nieuwe Monumenten', Middelheimmuseum, 23.05.2010-19.09.2010
boek